Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.2136/sh2010.3.0088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traffic Rate and Type on Soil Compaction in Sandy South Georgia Soils

Abstract: Soil compaction is one of the largest problems faced by modern mechanized agricultural and forestry operations. This makes research in the area of soil compaction critical. This study was undertaken to see how different types and levels of traffic have influenced soil compaction in sandy soils at the Valdosta State University Lake Louise field station south of Valdosta, GA. Four different traffic patterns were investigated in this study. The first area has relatively high vehicular traffic, the second more mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
5
6
0
Order By: Relevance
“…Nine of the 12 textural analysis samples had a sand texture, with the other three having a loamy sand texture. The textures determined during this study are in line with those found by Caverzasi et al (2004) and Williams and Brevik (2010) in Albany series soils near one of the sample sites for this study and are also consistent with the official range in characteristics for these soils (Stevens, 1979).…”
Section: Resultssupporting
confidence: 91%
“…Nine of the 12 textural analysis samples had a sand texture, with the other three having a loamy sand texture. The textures determined during this study are in line with those found by Caverzasi et al (2004) and Williams and Brevik (2010) in Albany series soils near one of the sample sites for this study and are also consistent with the official range in characteristics for these soils (Stevens, 1979).…”
Section: Resultssupporting
confidence: 91%
“…The decrease in bulk density with increasing depth between the on‐trail 5‐ to 10‐cm and 10‐ to 15‐cm depth intervals is believed to be due to intense compaction near the surface by traffic that was not translated into deeper portions of the soil. Similar phenomenon has been observed at other trafficked sites (Voorhees, 1983; Sharratt et al, 1998; Williams and Brevik, 2010).…”
Section: Resultssupporting
confidence: 85%
“…Given that conditions which may lead to soil compaction are so prevalent, it is not surprising that soil compaction has been studied extensively. Research on soil compaction has covered a wide range of topics—compaction by animals (e.g., Naeth et al, 1990; Greenwood et al, 1997); the effect of compaction on trees, crops, or pasture (e.g., Wert and Thomas, 1981; Assaeed et al, 1990; Sveistrup and Haraldsen, 1997); the effect of compaction on soil apparent electrical conductivity readings (Brevik and Fenton, 2004); compaction due to recreational activities (e.g., Monti and MacKintosh, 1979; Stohlgren and Parsons, 1986); compaction due to traffic (e.g., Voorhees, 1993; Foshee et al, 1997; Williams and Brevik, 2010; Labelle and Jaeger, 2011); and the effect of compaction on soil fauna (e.g., Boag, 1985; Bostrom, 1986). These examples serve to demonstrate that research on soil compaction has covered a wide range of topics, but they by no means cover all of the topics related to compaction that have been researched.…”
mentioning
confidence: 99%
“…Most of the research on human trampling impact has been conducted on recreational trails (Svajda et al, 2016) and in campsites (Tibor and Brevik, 2013), but there is no research on agricultural land. Recreational research has shown that high levels of human trampling causes negative effects on soil properties such as compaction (Godefroid and Koedam, 2004;Monti and MacKintosh, 1979;Stohlgren and Parsons, 1986), but can have a minimal impact at low levels (Tibor and Brevik, 2013;Williams and Brevik, 2010). There is a need to research how human trampling changes soil compaction and soil aggregate stability in agricultural soils and develop plans and strategies to reduce its impact.…”
Section: Discussionmentioning
confidence: 99%